Interpreter training: Devising a model for aptitude testing for simultaneous interpreters - Gambrell, Simoné; Lesch, Harold (Stellenbosch Papers in Linguistics Plus, 2021)
The proper selection and training of simultaneous interpreting candidates would ensure that they meet all essential requirements and are fully prepared to face any professional assignment they might encounter. Aptitude tests for entrance to training courses may be a step on the path to improving interpreting quality and strengthening the professionalisation of the field. As a result, this study aimed to design a comprehensive, custom-made aptitude test for simultaneous interpreting relevant for the South African context. A further aim for this test was for it to be used in practice to differentiate between those students who have the ability to succeed as interpreters and those who do not, in order to ultimately improve the quality of the professional field of interpreting. This aim was accomplished through a qualitative research design. First, a review was conducted on the available literature on interpreter aptitude testing. Further analysis showed that only eight of these tests had been proven to reliably predict aptitude for interpreting. Second, online surveys and in-person, semi-structured interviews were utilised to gather the opinions of interpreter trainers and potential interpreting students. The trainers were asked, among other questions, which cognitive and personality traits they would wish to test for in prospective students. The students were also asked, among other questions, to rate on a Likert scale their confidence in successfully completing the different available aptitude tests. Through this data, it was found that there is a need for aptitude testing for the training of simultaneous interpreting students in South Africa, and that both trainers and students advocated for its use. Moreover, it was possible to determine the most effective aptitude tests from among those that are available and, furthermore, those that would be easy to administer and complete.